Translating research evidence into clinical practice within a single breast imaging unit – A personal reflection. (October 2020) - Kelly, J.F.
Abstract: Health care organisations are required to deliver high quality evidence based and cost effective clinical care. Generating research evidence, appraising new published evidence and integrating it into clinical practice is time-consuming but an essential component in the continuous improvement of care delivery. This article is a personal reflection on the impact of research in clinical practice in a busy, single breast imaging unit from a number of different perspectives. It also highlights a number of benefits that are to be realised both from a service delivery perspective and across the whole staff team from engagement in such activity, which is an integral aspect of our work.